Between Skepticism and Identification: A Systematic Mapping of Adolescents' Persuasion Knowledge of Influencer Marketing. Issue 3 (3rd July 2022) - Borchers, Nils S.
Abstract: How well are adolescents prepared to competently cope with sponsored influencer content? This article provides a systematic mapping of influencer-specific dispositional persuasion knowledge in the five dimensions proposed by the persuasion knowledge model (PKM). In twenty-three focus groups with 132 German adolescents between eleven and fifteen years of age, the author found that adolescents are well aware of sponsored influencer posts, even if they might overestimate their knowledge. Specifically, the author observed a tension in adolescents between their knowledge that sponsored content is advertising and should be scrutinized skeptically and their identification with particular influencers.